Implementasi Perubahan Organisasi Dalam Kinerja Pegawai Di Sektor Pemerintah Desa Simo Kecamatan Soko Kabupaten Tuban - Hanum Regitawati; Melvi Noviza; Muhamad Muslih; Nadiya Eka Puspita Virginia; Nur Nadhifah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
this study is entitled "implementation of organizational changes in the performance of employees in the government sector of Simo village, soko district, tuban Regency". The purpose of this study is to explain and analyze the organizational strengthening carried out by the Tuban District Office as one of the agencies in Tuban Regency, as well as the excellent service provided by the office. This method uses a descriptive qualitative research approach in which researchers interviewed 2 sides, namely from the side of village officials and the community. Apart from the results of interviews, researchers also use literature research methods, namely research sourced from primary and secondary empirical data from journals, articles, or other literature. Based on the results of the study showed Simo village government has conducted planning and strategy development, adjustment between strategy and actual organizational conditions, implementation of strategy, maintenance and maintenance of organizational change, and reorientation and change of strategy and improve employee performance and improve service quality